2010
DOI: 10.4061/2010/290541
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Bovine Ephemeral Fever Outbreaks in Israel

Abstract: Outbreaks of bovine ephemeral fever (BEF) occurred in Israel in 1990, 1999, and 2004. The main patterns of BEF spread were similar in the 1990 and in 1999 epidemics, and the BEF virus was probably carried in vectors transported by air streams across the Rift Valley and the Red Sea. In the 2004 outbreak, the primary focus of the disease was the southern Mediterranean coastal plain and the disease agent was apparently brought by infected mosquitoes carried from their breeding site in the Nile Delta by the south-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
1
26
1
4
Order By: Relevance
“…and 100%, respectively [19]. Momtaz et al reported animal level incidence in the province of Khuzestan, Iran, to be higher than what we observed in this study [5], whereas others [21] reported similar findings to ours.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…and 100%, respectively [19]. Momtaz et al reported animal level incidence in the province of Khuzestan, Iran, to be higher than what we observed in this study [5], whereas others [21] reported similar findings to ours.…”
Section: Discussioncontrasting
confidence: 56%
“…It is considered as an endemic disease in Africa and most areas of the Middle East [18,19] being reported from Jordan, Syria, Iraq, Turkey, and Iran. In some African and Asian countries, the epidemic form of the disease has been reported as well [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…bef virus ( befv ), which was formerly thought to appear cyclically in Israel every seven to 15 years, reappeared in 1999, 2000, 2001 and 2004 (Yeruham and others 2002, 2003a, b, 2005). Akabane virus, the causative agent of the arthrogryposis and hydrancephaly/microencephaly syndromes, that appeared in the northern valleys of Israel in 1969/70 (Markusfeld-Nir and Mayer 1971, Kalmar and others 1975, Shimshony 1980), appeared again in 2001 and 2003 (Brenner and others 2004a, b).…”
mentioning
confidence: 99%
“…It has also been reported in australia (FINLaISON et al, 2010;St GeOrGe, 1997) and in most countries of africa and asia (BakhSheSh and aBDOLLahI, 2015;hSIeh et al, 2005;MOMtaZ et al, 2012;YerUhaM et al, 2002;ZaGhaWa et al, 2016) and Japan (katO et al, 2009;NIWa et al, 2015;OGaWa, 1992). In Turkey, BEF infection was first recorded in 1985 (GIrGIN et al, 1986).…”
mentioning
confidence: 93%